Epidemiological Feature of Visceral Leishmaniasis in China, 2004-2012 - Shuqing Zhao; Zhongjie Li; Sheng Zhou; Canjun Zheng; Huilai Ma (Tehran University of Medical Sciences, 2015)
Background: Visceral leishmaniasis (VL) remains an important public health problem in China. It is essential to elucidate the current epidemiological characteristics of VL for designing control policy. Methods: The data were obtained from China Disease Prevention and Control Information System from 2004 to 2012. Characteristics by major variables, such as age, gender, season and geography were analyzed using SPSS13.0. Results: The incidence of VL in China remained at a lower level in recent years. The outbreak appeared in xinjiang kashgar region in 2008. A total of 3337 VL cases were reported in China from 2004 to 2012, 97.03% of cases were concentrated in Xinjiang, Gansu and Sichuan provinces. The cases under 5 year-old accounted for 59.21%. concentrated in 3 ~ 5 months each year and annual December to January of next year The ratio of males to females was 1.67:1(2088:1249). The lag time between symptom onset and diagnosis of VL appeared a marked decrease after 2008, and were shorter in endemic provinces of Xinjiang, Gansu and Sichuan than non-endemic provinces. The case fatality rate was 2.99% (10/3337) during the study period. Conclusion: The reported cases of VL were concentrated in Xinjiang, Gansu, Sichuan provinces in China, 2004-2012. The onset was given priority to children. The lag time between symptom onset and diagnosis of VL were difference among years and provinces. Therefore, prevention and control measures should be focused on improving awareness and capacities of diagnosis and treatment, targeting high-risk people in high-risk areas.